Role of hospital supportive services in COVID-19 - Sodhi, Jitender; Satpathy, Sidhartha; Arora, Pankaj (International Journal of Infection Control, 2020)
Hospital Supportive Services complement the clinical services in any setting. They have a crucial role in mitigation of infection and delivery of safe care to the patients. The spectrum of hospital supportive services encompasses linen & laundry, dietary, Central Sterile Supply Department (CSSD), transport hospital stores, mortuary and engineering services. Each of these services has a significant role to help abort the ‘chain of transmission’ of COVID-19 infection across various patient care areas in the hospital, while providing them supportive services. The overall patient satisfaction greatly depends on the quality of hospital supportive services rendered to him during his stay. These Services usually work at the back end but their contribution in the overall care of a patient is no where less than that of the clinical services.